1961
DOI: 10.1039/tf9615701885
|View full text |Cite
|
Sign up to set email alerts
|

Primary photochemical processes in aromatic molecules. Part 6.—The absorption spectra and acidity constants of phenoxyl radicals

Abstract: Phenoxyl radicals and their derivatives have been prepared by flash photolysis in gaseous and liquid systems, by chemical oxidation and by photolysis of rigid solutions. Their spectra have been recorded and the longer wavelength system, expected on theoretical grounds, has been observed. Investigations of the spectrum as a function of pH show that these radicals are very weak bases and that, contrary to the interpretations of some other workers, the spectra observed under all conditions except those of very hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
107
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(122 citation statements)
references
References 1 publication
15
107
0
Order By: Relevance
“…Recently, difference spectra of tyrosine radicals from pulse radiolysis experiments have been presented (57). These spectra were largely shifted (up to 40 nm) to red wavelengths when compared to other in vitro spectra in a large body of literature (58,61,69,70) and to Y Z in PSII (see Figure 3), and the extinction coefficients in the UV in ref 57 were smaller, about 50-75% of the values obtained for the oxidation of tyrosine in vitro (58,61,69,70) and in PSII (see ref 57 and references therein). Furthermore, the contribution of the reduced state to the oxidized-minus-reduced spectra seemed to be much higher than in other in Vitro and in vivo spectra (see above).…”
Section: Raw Absorption Difference Spectra and Their Deconvolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, difference spectra of tyrosine radicals from pulse radiolysis experiments have been presented (57). These spectra were largely shifted (up to 40 nm) to red wavelengths when compared to other in vitro spectra in a large body of literature (58,61,69,70) and to Y Z in PSII (see Figure 3), and the extinction coefficients in the UV in ref 57 were smaller, about 50-75% of the values obtained for the oxidation of tyrosine in vitro (58,61,69,70) and in PSII (see ref 57 and references therein). Furthermore, the contribution of the reduced state to the oxidized-minus-reduced spectra seemed to be much higher than in other in Vitro and in vivo spectra (see above).…”
Section: Raw Absorption Difference Spectra and Their Deconvolutionmentioning
confidence: 99%
“…The reasons for these discrepancies are still unknown. We preferred to use the more consistent set of spectra from the elder literature (58,61,69,70) for our simulations.…”
Section: Raw Absorption Difference Spectra and Their Deconvolutionmentioning
confidence: 99%
“…159,160) Radical cations of phenol derivatives, which are precursors of phenoxy radicals in many cases, had been more elusive than phenoxy radicals. 158,[161][162][163][164][165][166][167][168] The absorption maxima of radical cations of phenol and p-cresol are at 440 and 430 nm, respectively. 169) The radiation chemistry of the model compounds for protected PHS such as methoxybenzene (anisole), methoxytoluene, and dimethoxybenzene has also been intensively investigated using pulse radiolysis, [170][171][172][173] photolysis, 174,175) chemical oxidation, [176][177][178] and electrochemical methods.…”
Section: Aromatic Polymersmentioning
confidence: 99%
“…Phenoxy radicals, which are stable decomposition intermediates of phenols, were first observed in the 1950s. 157) Land et al reported that phenoxy radicals are very weak bases 158) and show a characteristic absorption band. 159,160) The absorption maxima of phenoxy radicals of phenol and p-cresol in water are at 400 and 405 nm, respectively.…”
Section: Aromatic Polymersmentioning
confidence: 99%
“…Only with 4,4′-biphenol was a transient species with an absorption maximum at 400 nm observed. We used flash photoysis to achieve the one-electron oxidation of 4,4′-biphenol: Phenols are known to photolyse by ejecting a photoelectron (10). Figure 2 shows the flash photolysis of 4,4′-biphenol: Within nanoseconds of the flash, a product that absorbs strongly at 400 nm is formed.…”
Section: Resultsmentioning
confidence: 99%